1979
DOI: 10.1007/bf00432291
|View full text |Cite
|
Sign up to set email alerts
|

Drugs and the discrimination of duration

Abstract: The effects of lysergic acid diethylamide (LSD), d-amphetamine (AMP), chlorpromazine (CPZ), and the most active isomer of marihuana (delta9 - THC) on timing behavior were analyzed with a two-choice, discrete trial procedure in which pigeons were trained to discriminate visual stimuli that differed with respect to duration ('long' vs. 'short'). LSD (0.01, 0.04, 0.16 mg/kg) decreased response speed (increased latency), but otherwise had no significant effects on performance of the discrimination. d-Amphetamine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Appel & Dykstra, 1977;Katz, 1982), the degree of stimulus control has been shown to modify the behavioral effects of chlorpromazine and promazine (Altman, Appel, & McGowan, 1979;Dykstra, 1979;Hernandez & Appel, 1979;Katz, 1983;Ksir & Slifer, 1982). For example, Katz (1983) showed that promazine did not affect stimulus control when responding was under control of an intense stimulus light but that it decreased stimulus control when responding was controlled by a relatively weak stimulus light.…”
Section: Discussionmentioning
confidence: 99%
“…Appel & Dykstra, 1977;Katz, 1982), the degree of stimulus control has been shown to modify the behavioral effects of chlorpromazine and promazine (Altman, Appel, & McGowan, 1979;Dykstra, 1979;Hernandez & Appel, 1979;Katz, 1983;Ksir & Slifer, 1982). For example, Katz (1983) showed that promazine did not affect stimulus control when responding was under control of an intense stimulus light but that it decreased stimulus control when responding was controlled by a relatively weak stimulus light.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of amphetamine have been studied using estimation procedures. With discrete-trial estimation procedures, amphetamine decreased accuracy of discrimination and increased response position bias at doses that did not alter response probability [Altman et al, 1979;Rapp and Robbins, 1976;Stubbs and Thomas, 19741. Another effect has been a shift in the psychometric function, which is interpreted as increasing the speed of a hypothetical internal clock [Maricq et al, 19811. The goals of the present experiment were to assess the usefulness of a titration procedure to measure the effects of drugs on duration discrimination.…”
Section: Effects Of Pentobarbital and (I-amphetamine On Duration Discmentioning
confidence: 99%
“…The stimulus employed may be in any modality, for example visual (Grilly et al 1980;Milar 1981;West et al 1982;Andrews and Sahgal 1984), auditory (Dykstra and Appel 1974;Slangen 1983, 1984) or tactile, e.g., shock (Dykstra 1980;Grilly et al 1980;Grilly 1981). These procedures have been employed to assess the effects on discrimination of a wide variety of drugs, such as LSD (Dykstra and Appel 1974;Hernandez and Appel 1979), barbiturates (Grilly et al 1980), morphine (Grilly et al 1980;Grilly 1981 ;West et al 1982;Slangen 1983, 1984;Moerschbaecher et al 1984), and amphetamine (Altman et al 1979;Grilly et al 1980;Evenden and Robbins 1983;Slangen 1983, 1984). Procedures of this type allow several different components of performance to be assessed, for example changes * Present address" Department of Neuropsychopharmacology, Schering AG, D-t000 Berlin 65 Offprint requests to: S.G. Holtzman in overall discriminative ability, response bias, and response latencies.…”
mentioning
confidence: 99%
“…Several studies have indicated dose-related changes in discrimination performance Slangen 1983, 1984), whereas others have seen none (Altman et al 1979, Grilly et al 1980. These results may be due to the ability of amphetamine to induce stereotypic behavior in animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation